Antimicrobial resistance in ESBL and indicator E. coli, Campylobacter spp.,Salmonella spp., methicillin-resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis and faecium isolated from food and food-producing animals (primary production) in 2023 - Cristina Garcia-Graells; François Bricteux; Inge Van Damme; Cécile Boland; Carole Kowalewicz (2024)
In Belgium, the FASFC monitors the evolution of antimicrobial resistance (AMR) in food and foodproducing animals (primary production). Resistance in the zoonotic bacteria Salmonella spp. and Campylobacter spp. and in methicillin-resistant Staphylococcus aureus (MRSA) as well as resistance in indicator bacteria Escherichia coli, Enterococcus faecalis and Enterococcus faecium was monitored in 2023. Moreover, a specific monitoring of presumptive extended spectrum βlactamases/AmpC/carbapenemase producing E. coli is done on strains isolated from food-producing animals and meat derived thereof. Microbiological resistance was assessed using epidemiological cutoff values (ECOFF) according to EUCAST (European Committee on Antimicrobial Susceptibility Testing). In 2023, the European Commission Implementing Decision 2020/1729 of the 17th of November 2020 was applicable for the determination of the epidemiological cut-off values as well as for the selection of antimicrobial panels (a.o. EUVSEC3/EUCAMP3). In Campylobacter jejuni isolated from poultry meat, the predominant resistance profiles included ciprofloxacin combined with tetracycline. However, resistance to tetracycline was lower in 2023 (42.9%) than in 2022 (54.3%). Resistance to ertapenem in C. jejuni increased in 2022 (13.0%) and again in 2023 (14.3%) in comparison with 2021 (11.1%) when the antibiotic was added to the test panel. Multidrug resistance in C. jejuni decreased to 10.2% in 2023 compared to 15.2% in 2022. In Campylobacter coli isolated from poultry meat, while ciprofloxacin resistance decreased in 2023, resistance to erythromycin, ertapenem and tetracycline increased, thus increasing the multidrug resistance rate as well from 39,1% in 2022 to 48.6%. In primary production, the monitoring of Campylobacter coli in fattening pigs showed overall stable resistance levels in comparison with 2022 except for a decreased resistance to ciprofloxacin (from 45.7% to 40.8%) and to erythromycin (from 19.5% to 10.9%). However, in C. coli isolated from veal calves, resistances to ciprofloxacin, ertapenem, gentamicin and tetracycline were lower in 2023 than in 2022 but resistances to chloramphenicol and erythromycin were higher. In C. jejuni, resistance to ertapenem keeps increasing since its addition in 2021. Resistances to gentamicin and tetracycline increased in 2023 as well. However, resistances to ciprofloxacin, erythromycin and chloramphenicol decreased in 2023.   Overall, as seen in previous reports, antimicrobial resistance levels are lower in C. jejuni than in C. coli. In 2023, Salmonella spp. recovered from food matrices have been analysed by whole genome sequencing (WGS). The highest levels of predicted antimicrobial resistance considering all serotypes and all matrices are to sulfamethoxazole (57%), followed by ampicillin (48%), tetracycline (43%) and trimethoprim (30%). Resistance to (fluoro)-quinolones associated to the qnrB gene was mainly predicted in isolates from broiler neck skin (11.2%) all belonging to serotype Chester (ST1954). Two isolates showed a predicted resistance to 3rd generation cephalosporins, one isolate from sunflower seeds belonging to the serotype Kentucky (ST198). This isolate harbored a blaCTX-M-14b together with the following genes: aac(3)-Id; aac(6')-Iaa, aadA7; aph(3'')-Ib, aph(3')-Ia; aph(6)-Id; sul1; tet(A) which confer a multidrug resistant profile including sulfamethoxazole, tetracycline and gentamicin among other aminoglycosides. The second isolate harboring a gene conferring resistance to extended spectrum β-lactams was isolated from cut poultry meat and belonged to the serotype Infantis (ST8662). The isolate harbored the following genes: blaCTX-M-3, aac(6')-Iaa; aadA1; aadA1; dfrA14; sul1; tet(A) conferring  a multi drug resistance profile including extended spectrum β-lactams, aminoglycosides, trimethoprim, sulfonamides and tetracyclines.   Resistance to colistin is rare, and was only predicted in one isolate from broiler neck skin. The isolate belonged to Salmonella Paratyphi B var. Java (ST28) and harbored the mobile colistin  resistance gene mcr-9.1. The isolate carried the following genes as well, aac(6')-Iaa; dfrA1; formA; lnu(F); aph(3')-Ia; sul1; and qacE conferring a multidrug resistant profile including trimethoprim, fosfomycin, lincosamide, aminoglycosides, sulfonamides, and quaternary ammonium biocides. In Salmonella spp. isolated from food-producing animals, the most prevalent serotypes found in samples from pig caecal content were Monophasic Typhimurium (31%), Typhimurium (26%) and Derby (20%). Resistances to all antimicrobials but trimethoprim and amikacin, which is detected for the first time in this matrix, decreased in 2023. In the 3 Salmonella spp. isolates retrieved from veal calves caecal content, 2 belonged to the serovar Typhimurium and the last one to its monophasic variant. In both matrices, no resistance to 3rd generation cephalosporins, colistin or meropenem was detected in 2023. In 2023, all Salmonella spp. isolates from fattening pigs and bovines were analysed by WGS as well. Considering all serotypes, the resistance pattern predicted for isolates from fattening pigs were as follows: tetracycline (53.50%), ampicillin (46.51%), sulfamethoxazole (44.19%) and trimethoprim (27.91%). The gene aac(6')-Iaa was found in all genomes independently of the serovars. This gene encodes for a chromosomal aminoglycoside acetyltransferase which confers resistance to aminoglycosides. However, aac(6′)-Iaa and similar genes usually are transcriptionally silent and rarely become transcriptionally active. The mere presence of this gene does not confer aminoglycoside resistance in Salmonella. All but two isolates belonging to the serovar Typhimurium and its variant monophasic harbored the following resistance genes blaTEM-1B, tet (B or M) and sul (1 or 3) conferring resistance to penicillins, tetracyclines and sulfamides. Other serotypes found in fattening pigs, such as S. Derby and S. Rissen were predicted to be occasionally resistant to the above mentioned antimicrobials and not any other resistance was predicted.   None of the isolates from either category of food-producing animals were predicted to be resistant to 3rd generation cephalosporins, ciprofloxacin or colistin. No known associated genes to the mentioned antimicrobials were found in any of the isolates.   The specific monitoring of ESBL, AmpC and carbapenemase producing E.coli was performed in broilers, turkeys, fattening pigs and bovines at slaughterhouse and in meat derived from these 4 categories of food producing animals at retail. In 2023, the highest prevalence of ESBL E.coli was found in caecal content from bovines (66.60%) followed by broilers (61.72%) and fattening pigs (29.26%). We have observed a significant decrease in the prevalence of ESBL E. coli isolated from broilers and fresh meat. As reported in previous years, the prevalence of ESBL E. coli on broiler fresh meat was the highest (45.51%) among the fresh meat categories followed by bovine fresh meat (3.19%) and pig meat (1.92%) which remains low. No meropenem-resistant isolates were detected in 2023. However, ESBL E.coli isolated from these matrices showed extremely high levels of multidrug resistance (>80%).  The most frequent determinants encoding for ESBL enzymes found in isolates from broilers at slaughterhouse and fresh poultry meat were blaSHV-12, bla CTX-M-55 and bla TEM-52.  Isolates from bovines and fattening pigs carried genes encoding for enzyme production CTX-M group 1. In addition, a significant number of isolates from bovines carried the gene blaCTX-M-2, suggesting this category of food producing animals as a reservoir of this particular mechanism of resistance.  In indicator E.coli, in comparison with 2022 an overall decreased resistance to most antibiotics was detected in food-producing animals: in broilers, veal calves of less than one year and fattening pigs sampled at the slaughterhouse as well as in laying hens, breeding hens and meat bovines of less than 7 months old sampled at the farm. The highest prevalences to the critically important antimicrobials 3rd generation cephalosporins and (fluoro)quinolones were detected in E. coli from broiler caecal content sampled at the slaughterhouse but were lower in 2023 than in previous years. Low or very low rates of 3 resistance to amikacin were detected in E. coli isolated from pig caecal content every year since its addition in 2021. And low colistin resistance was also detected continuously over the previous years in E. coli isolated from veal calves caecal content. At the level of the farm, the highest resistance to (fluoro)quinolones was found in E. coli isolated from breeding hens while resistance to 3rd generation cephalosporins was detected in 3 E. coli isolates from fecal samples of bovine animals, and in one isolate from breeding hens and in one isolate from laying hens. No resistance to meropenem was detected in any of the indicator E. coli isolates.  Monitoring of methicillin-resistant Staphylococcus aureus (MRSA) was carried out in broilers, laying hens and fattening turkeys on farm in 2023. The bovines and pigs were monitored in 2021 and 2022, respectively (3 years-rotation). The aim of this monitoring is to assess the MRSA prevalence in these animal categories and determine the genotypes (STs and spa-types) of  the collected MRSA isolates together with their AMR and virulence genes. In 2023, the MRSA prevalence was very low in broilers (1.0%) and moderate in fattening turkeys (18.5%) while null in laying hens. The MRSA prevalence remains stable since 2011 in broiler and laying hens and compared to 2020 (first year of turkey monitoring) in fattening turkeys.  In 2023, all isolates (n=1 from broilers, n=5 from fattening turkeys) were genotyped as LA-MRSA according to their STs/spa-types combinations. All MRSA isolated in 2023 were harboring the mecA gene and  the tet(M) tetracycline resistance gene, which are also characteristics of LA-MRSA. Several other resistance genes were observed and detailed in the results. All the 6 MRSA isolates were genetically multi-drug resistant (i.e., carrying genes conferring resistance to at least 3 different antibiotic classes). However, in 2023, no gene encoding resistance to the critically important antibiotics (linezolid and vancomycin) was detected. Moreover, several virulence genes associated with the human immune evasion cluster (sak, scn), associated with toxins (hlgA, hlgB, hlgC and selw) and/or exoenzymes (aur) were detected among the 6 MRSA isolates analysed in 2023. One LA-MRSA isolate from fattening turkeys carried the sak and scn genes associated with the human immune evasion cluster and several genes associated with toxins (hlgA, hlgB, hlgC, and selw) and exoenzyme (aur). This isolate would probably not have been recently transmitted from humans to turkeys, given the livestock-associated genetic background and the carriage of the tet(M) gene. The genes associated with the immune evasion cluster were not observed in the other isolates. The presence of MRSA in food-producing animals and their carriage of several AMR and virulence genes represents a public health risk. The monitoring of Enterococcus faecalis and Enterococcus faecium, organized in Belgium in foodproducing animals between 2011 and 2013, and resumed in 2019, continued. Investigation of the AMR prevalence in these commensal indicator bacteria was assessed in order to complete the picture of the situation of antimicrobial resistance within our farms and slaughterhouses. Enterococci are also considered to be reservoirs of antibiotic resistance genes, present in both humans and animals. In 2023, the prevalences of enterococci species by animal category were similar to those observed in previous years. Indeed, Enterococcus faecium was more frequently isolated than Enterococcus faecalis within the samples of breeding hens (88.4%), laying hens (72.0%), veal calves (54.8%) and pigs (62.3%). Conversely, E. faecalis was isolated more frequently than E. faecium in broiler (68.8%) samples.  The antimicrobial susceptibility tests carried out this year showed that, in general, the resistance rates observed in Enterococcus faecalis and Enterococcus faecium within the various animal matrices studied have remained stable since 2019, with a few exceptions (significant decreases). Significant decreases in antimicrobial resistance were observed in 2023 for erythromycin in E. faecalis isolated from breeders, and for tetracycline in E. faecalis isolated from broilers in comparison to 2021. Resistance to tetracycline, erythromycin and to quinupristin/dalfopristin were still the most observed resistances, both in E. faecalis and E. faecium. Resistance to linezolid (n=16), a critical antibiotic for human health, was also observed in 2023, in 12 E. faecalis isolated from veal calves (n=11), pigs (n=1) and in 4 E. faecium isolated from pigs (n=3) and veal calves (n=1). Daptomycin resistance was low and observed in E. faecalis isolated 4 from breeders (n=1), layers (n=1) and pigs (n=1). Multidrug resistance was mainly observed in broilers and veal calves with 53.6% of multi-resistant E. faecium and 63.3 % of multi-resistant E. faecalis, respectively. No resistance to teicoplanin, tigecycline or vancomycin was observed in 2023. In 2023, some enterococci were sequenced by WGS. This report also presents these WGS results and the detailed characterization of these strains, including the detection of optrA gene encoding linezolid resistance. Taking together all results from both gram-negative (E. coli) and gram-positive indicators (enterococci) isolated from food-producing animals, resistance rates showed overall a decrease in 2023 in E. coli and a global status quo in enterococci (except 2 particular significant decreases).
Keywords: antimicrobial resistance (AMR); Campylobacter; E. coli; Enterococcus; MRSA; Salmonella

Antimicrobial resistance in ESBL and indicator E.coli, Campylobacter spp., Salmonella spp., methicillin-resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis and faecium isolated from food and food-producing animals (primary production) in 2022 - Cristina Garcia-Graells; François Bricteux; Inge Van Damme; Cécile Boland; Carole Kowalewicz (2023)
In Belgium, the FASFC monitors the evolution of antimicrobial resistance (AMR) in food and foodproducing animals (primary production). Resistance in the zoonotic bacteria Salmonella and Campylobacter and in methicillin-resistant Staphylococcus aureus (MRSA) as well as resistance in indicator bacteria Escherichia coli, Enterococcus faecalis and Enterococcus faecium was monitored in 2022. Moreover, a specific monitoring of presumptive extended spectrum betalactamases/AmpC/carbapenemase producing E.coli is done on strains isolated from food-producing animals and meat derived thereof. Microbiological resistance was assessed using epidemiological cutoff values (ECOFF) according to EUCAST (European Committee on Antimicrobial Susceptibility Testing). In 2022, the European Commission Implementing Decision 2020/1729 of the 17th of November 2020 was applicable for the determination of the epidemiological cut-off values as well as for the selection of antimicrobial panels (EUVSEC3/EUCAMP3). In Campylobacter jejuni isolated from poultry meat, the predominant resistance profiles included ciprofloxacin combined with tetracycline. An increase in resistance to these antibiotics as well as to ertapenem and erythromycin was seen in 2022. Multidrug resistance in C. jejuni also increased in 2022 up to 13% compared to 4,4% in 2021. In Campylobacter coli from poultry meat, while ciprofloxacin resistance increased in 2022, resistance to erythromycin, ertapenem and tetracycline slightly decreased, thus lowering the multidrug resistance rate as well from 43,48% in 2021 to 39,13%. In primary production, the monitoring of Campylobacter coli in fattening pigs showed overall stable resistance levels except for an increased resistance to erythromycin and a first detection of low chloramphenicol resistance. In 2022, 20% of the isolates were resistant to the macrolide erythromycin compared to 9% observed in 2021. However, in C. coli isolated from veal calves, resistances to erythromycin, ertapenem and chloramphenicol were lower in 2022 than in 2021 but resistances to ciprofloxacin and gentamicin were higher. In C. jejuni, resistances to erythromycin, ertapenem, gentamicin and chloramphenicol increased but resistances to ciprofloxacin and tetracycline remained stable. Overall, as seen in previous reports, antimicrobial resistance levels are lower in C. jejuni than in C. coli. In 2022, considering all Salmonella spp. recovered from food matrices, the most prevalent serotypes were S. Infantis recovered mainly from fresh meat from poultry and S. Monophasic Typhimurium from fattening pigs and veal calves. Resistance levels increased for 6 out of the 15 tested antimicrobials in Salmonella isolated from food matrices, resistance to amikacin was also detected for the first time in processed meat (cold cuts) but resistance to (fluoro)quinolones decreased compared to 2021. In foodproducing animals however, resistance to (fluoro)quinolones increased in 2022, especially in poultry. Resistance to third generation cephalosporins was only found in one isolate of S. Paratyphi B var L(+) tartrate(+) from poultry cutted meat and one S. Dublin recovered from veal calves. Overall, resistance to colistin is very low, only two isolates of S. Dublin recovered one from poultry cutted meat and another from veal calves were resistant to colistin. The specific monitoring of ESBL, AmpC or carbapenemase producing E.coli was carried out in broilers, turkeys, fattening pigs and veal calves and in meat derived from these 4 categories of animals. As it has been the case in the previous years, the highest prevalence of ESBL E.coli was found in broilers (75%) followed by turkeys (64%), veal calves (64%) and fattening pigs (35%). In fresh meat from foodproducing animals as well, the prevalence was the highest in fresh meat from broilers (58%) followed by fresh meat from turkeys (24%). The prevalence was much lower in fresh meat from veal calves (2%) and fresh meat from fattening pigs (2%). No meropenem-resistant isolates were detected in 2022. However, ESBL E.coli isolated from these matrices showed extremely high levels of multidrug resistance (>80%). 2 In indicator E.coli, in comparison with 2021 an overall increased resistance was detected in most categories of food-producing animals, especially in isolates from faeces samples of laying hens, breeding hens and bovines at the farm level. (Fluoro)quinolones resistance also increased in isolates from caecal samples of broilers, veal calves, and fattening pigs taken at the slaughterhouse. However, resistance to critical antimicrobials such as colistin, tigecycline, cephalosporins and meropenem remains very low or non-existant in the different matrices in 2022. Also, in E.coli isolated from caecal samples of fattening turkeys, the levels of resistance to most antimicrobials were lower in 2022 than in 2021. Monitoring of methicillin-resistant Staphylococcus aureus (MRSA) was carried out in fattening pigs and sows on farm in 2022. The bovines and poultry were monitored in 2021 and 2020, respectively (3 yearsrotation). The aim of this monitoring is to assess the MRSA prevalence in these animal categories and determine the genotypes (STs and spa-types) of 170 of collected MRSA isolates together with their AMR and virulence genes. Several changes in the methodology used for the monitoring of MRSA have been made in 2022, including a new isolation method and the study of AMR through NGS rather than phenotypic susceptibility testings. The 2022 data will now serve as a new baseline for analyzing future trends. The extremely high prevalence (87.9%) observed in fattening pigs and, in a lesser extent, the very high prevalence observed in sows (52.6%), in 2022 with the new isolation method is a matter of concern.  In 2022, all but one isolate were genotyped as LA-MRSA according to their STs/spa-types combinations. The latter isolate is likely to belong to LA-MRSA as well, according to our investigation. All MRSA isolated were harboring the mecA gene and at least one tetracycline resistance genes, which are also characteristic of LA-MRSA. Several other resistance genes were observed. Of particular concern is the carriage of the cfr gene, encoding a.o. resistance to the critically important antibiotic linezolid, observed again in 2022 in 3 isolates (n=1 sows and n=2 fattening pigs). In addition to AMR genes, qac (precisely, qacG and qacJ) genes mediating resistance to quaternary ammonium compounds were observed in some MRSA isolates in 2022. Moreover, several virulence genes associated with the immune evasion cluster (sak, scn), toxins (hlgA, hlgB, hlgC, seb and selw) and exoenzymes (aur) were detected. One sow isolate belonging to the ST398-t034 LA-MRSA type carried the sak and scn genes associated with the human immune evasion cluster and several genes associated with toxins (hlgA, hlgB, hlgC and selw) and exoenzyme (aur). This isolate did not carry critically antimicrobial resistance gene (no cfr gene), neither qac disinfectant resistance gene. The genes associated with the immune evasion cluster were not observed in the other isolates. The detection of the seb gene encoding an exotoxin known to be the source for multiple pathologies in humans in an isolate from fattening pigs highlights the importance of monitoring these different virulence factors in the future. The presence of MRSA in foodproducing animals and their carriage of several AMR and virulence genes represents a public health risk.  The monitoring of Enterococcus faecalis and Enterococcus faecium, organized in Belgium in foodproducing animals between 2011 and 2013, and resumed in 2019, continued. Investigation of the AMR prevalence in these commensal indicator bacteria was assessed in order to complete the picture of the situation of antimicrobial resistance within our farms and slaughterhouses,. Enterococci are also considered to be reservoirs of antibiotic resistance genes, present in both humans and animals. In 2022, the prevalences of enterococci species by animal category were similar to those observed in previous years. Indeed, Enterococcus faecium was more frequently isolated than Enterococcus faecalis within the samples of breeding hens (85.6%), laying hens (69.9%), veal calves (64.0%) and pigs (66.4%). Conversely, E. faecalis was isolated more frequently than E. faecium in broiler (65.4%) and turkey (92.0%) samples.  The antimicrobial susceptibility tests carried out this year showed that, in general, the resistance rates observed in Enterococcus faecalis and Enterococcus faecium within the various animal matrices studied have remained stable since 2019, with a few exceptions (significant decreases). Significant decreases in antimicrobial resistance were observed for chloramphenicol in E. faecalis isolated from veal calves, and for ampicillin in E. faecium isolated from broilers in 2022. Resistance to tetracycline, erythromycin and to quinupristin/dalfopristin were still the most observed resistances, both in E. faecalis and E. 3 faecium. Resistance to linezolid (n=18), a critical antibiotic for human health, was also observed in 2022, in 13 E. faecalis isolated from veal calves (n=11), pigs (n=2) and in 5 E. faecium isolated from pigs (n=2), veal calves (n=2) and breeding hens (n=1). No resistance to teicoplanin or vancomycin was observed in 2022. Daptomycin resistance was very low in 2022 but it could be related to the modification of its threshold in 2021. Tigecycline resistance was observed for the first time since 2019 (n=2). Multidrug resistance (resistance to at least 3 antimicrobial classes) was mainly observed in broilers and veal calves with 60.3% of multi-resistant E. faecium and 60.2% of multi-resistant E. faecalis, respectively. In addition, strains accumulating the higher number of different antimicrobial resistances were isolated from veal calves, with a maximum of 6 different resistances observed in E. faecalis and E. faecium. In 2022, some enterococci were completely sequenced by Next-generation sequencing (NGS). This report also presents these NGS results and the detailed characterization of these strains, including the detection of optrA and poxtA genes encoding linezolid resistance.
Keywords: Antimicrobial resistance; Campylobacter; E. coli; Enterococcus; MRSA; Salmonella

The AMR-ARRAY: A modular bead array detecting β-lactam, (fluoro) quinolone, colistin, aminoglycoside and macrolide resistance determinants in Gram-negative bacteria. - Michaël Timmermans; Samuel Latour; Pieter-Jan Ceyssens; Cristina Garcia-Graells; Carole Kowalewicz; David Fretin; Denis, Olivier; P Wattiau; Cécile Boland (J Microbiol Methods, 2022)
The aim of this study was to develop a highly multiplexed bead array to detect genes and/or mutations frequently associated with resistance to antimicrobials of the β-lactam, (fluoro)quinolone, colistin, macrolide and aminoglycoside families in Enterobacteriaceae such as Escherichia coli, Shigella spp. and Salmonella spp. Ligase Chain Reaction and the Luminex® technology were combined in a 53-plex assay designed to target selected genetic markers with 3 internal controls. The AMR-ARRAY consistently detected resistance determinants as compared to phenotypically expressed resistance for 94.7% (856/904) of the assessed resistances. When compared to resistance profiles inferred from whole genome sequencing results, the AMR-ARRAY showed a selectivity and specificity of 99.3% and 100%, respectively. The strong features of the AMR-ARRAY are (i) its competitive cost, currently 18€/sample (ii) its wide analytical scope, currently 50 markers covering 5 antimicrobial families, (iii) its robust and user-friendly design consisting in a single-tube assay conducted in 4 successive steps (iv) its relatively short turnaround time, less than 8 h (v) its ability to detect allelic variability at critical SNPs (vi) its open access and easily upgradable design, with probes sequences, procedure and software source code freely available. The use of the AMR-ARRAY as a screening method in official antimicrobial resistance monitoring could improve the granularity of the collected data and pinpoint remarkable isolates harbouring unusual resistance determinants thereby enabling fit-for-purpose selection of isolates for Whole Genome analysis.
Keywords: Aminoglycosides; Anti-Bacterial Agents; beta-Lactams; Colistin; Drug Resistance, Bacterial; Escherichia coli; Gram-Negative Bacteria; Macrolides; Quinolones

An in‐house 45‐plex array for the detection of antimicrobial resistance genes in Gram‐positive bacteria - Carole Kowalewicz; Michael Timmermans; David Fretin; P Wattiau; Cécile Boland (MicrobiologyOpen, 2022)
Keywords: Enterococcus; optrA; poxtA; staphylococcus; vanA; vanL

La résistance antimicrobienne chez les E. coli BLSE et Commensales, Campylobacter spp., Salmonella spp., Staphylococcus aureus résistants à la méthicilline (MRSA) et Enterococcus faecalis et faecium isolés des populations d’animaux producteurs d’aliments - Cristina Garcia-Graells; François Bricteux; Inge Van Damme; Cécile Boland; Carole Kowalewicz; Koenraad Van Hoorde; David Fretin; Katelijne Dierick (2022)

La résistance antimicrobienne chez les E. coli BLSE et Commensales, Campylobacter spp., Salmonella spp., Staphylococcus aureus résistants à la méthicilline (MRSA) et Enterococcus faecalis et faecium isolés des populations d’animaux producteurs d’aliments - Cristina Garcia-Graells; François Bricteux; Cécile Boland; Carole Kowalewicz; Koenraad Van Hoorde; David Fretin; Katelijne Dierick (LNR AMR Sciensano, 2021)
En Belgique, l’AFSCA surveille la situation de la résistance antimicrobienne (AMR) à la fois dans les denrées alimentaires que chez les animaux producteurs d’aliments (production primaire). La résistance chez les bactéries zoonotiques Salmonella et Campylobacter et chez les Staphylococcus aureus résistants à la méthicilline (MRSA), ainsi que la résistance chez les bactéries indicatrices Escherichia coli, Enterococcus faecalis et Enterococcus faecium ont été surveillées en 2020. Les surveillances des Salmonella, Campylobacter et MRSA ont été effectuées uniquement chez la volaille en 2020. De même, une surveillance spécifique comprenait l'évaluation des niveaux d’E. coli producteurs présumés de bêta-lactamases à spectre étendu (BLSE)-/AmpC-/carbapénémases provenant d'animaux destinés à l'alimentation et des viandes provenant de ces catégories d’animaux a été aussi réalisée. La résistance microbiologique a été évaluée à l'aide des valeurs seuils épidémiologiques (ECOFF).   Chez Campylobacter jejuni isolés à partir de la viande de volaille une diminution de la résistance est remarquée pour les fluoro(quinolones) (60%) et la tétracycline (40%). De même une augmentation du nombre d’isolats sensibles à tous les antibiotiques testés a été remarquée en 2020. Les taux de résistance ont également été déterminés pour Campylobacter coli isolés à partir de la viande de volaille. Le profil de résistance observé est similaire à celui de C. jejuni bien que le niveau de prévalence de la résistance soit supérieur chez C. coli que C. jejuni. La surveillance de Campylobacter jejuni dans la matière fécale de poulets de chair montre un profil de résistance similaire à ceux retrouvés dans les viandes de volaille. Ce profil de résistance comprend les fluoro(quinolones) et la tétracycline et a été retrouvé dans 60% des isolats.   Chez Salmonella spp. provenant de carcasses de volailles à l’abattoir, le sérovar prédominant est Infantis, comme dans les années précédentes, et le taux de multirésistance est très élevé (88.52%). Un profil commun de résistance à l’ampicilline, sulfaméthoxazole, tétracycline et fluoro(quinolones) se retrouve fréquemment chez ce sérotype. La résistance aux céphalosporines de troisième génération a été détectée exclusivement dans un isolat de S. Minnesota.   Une surveillance spécifique d’E. coli productrices de BLSE, AmpC ou de carbapénémases a été menée dans les populations d’animaux, volailles, porcs d’engraissement et bovins de moins d’un an et dans les viandes fraiches de ces 3 populations d’animaux. Comme attendu, le taux de prévalence le plus élevé est retrouvé chez la volaille (79%), suivi des bovins de moins d’un an (76%) et des porcs d’engraissement (44%). En ce qui concerne les viandes fraiches des 3 catégories d’animaux précédentes, le taux le plus élevé a été retrouvé chez la viande de volaille (50.4%), suivi de la viande de bœuf (2.68%) et de la viande de porc (2.02%). Malgré une prévalence très basse chez la viande de bœuf et de porc, les isolats montrent une forte multirésistance. Aucun isolat n’a été isolé de la surveillance spécifique aux carbapénémases présumées et aucun n’a été détecté résistant au méropénème.   Chez les E. coli indicateurs isolés à partir de matière fécale dans les trois populations d’animaux producteurs de viande à l’abattoir, le taux de résistance aux antibiotiques de dernier choix (colistine, tigécycline et méropénème) était très faible ou inexistant. A noter, la diminution progressive de la résistance aux fluoro(quinolones) chez la volaille (50%), les bovins (20%) et les porcs d’engraissement (<10%). En ce qui concerne les céphalosporines de troisième génération, une résistance <10% a été retrouvée pour les trois catégories d’animaux.   La surveillance des Staphylococcus aureus résistants à la méthicilline (MRSA) chez les animaux producteurs de denrées alimentaires a été réalisée chez la volaille en 2020. En effet, la résistance présente chez nos animaux est importante à évaluer puisque des échanges de MRSA et potentiellement des résistances associées de l’animal vers l’homme, et inversement, ont été décrits. Cette année, la prévalence globale observée chez la volaille reste faible (3.8%, 4/106 échantillons, IC95% [0.1-7.4%]) et stable depuis 2011. Les 4 échantillons positifs pour MRSA ont été typés génétiquement comme appartenant au complexe clonal CC398, type génétique caractéristique des clones MRSA d’origine animale (LA-MRSA) ainsi qu’au spa-type t011, déjà rapporté chez la volaille en Belgique lors des surveillances précédentes (2011, 2014 et 2017) et connu dans la littérature pour être associé au complexe clonal CC398 ou aux LA-MRSA (Hetem et al.,2013, Köck et al., 2013, Vandendriessche et al, 2013, Sharma et al., 2016). Toutes les souches MRSA isolées en 2020 étaient résistantes à la céfoxitine et à la pénicilline, comme attendu, ainsi qu’à la tétracycline, ce qui est également caractéristique des LA-MRSA (Crombé et al., 2013). Un profil de résistance différent a été observé pour chacune des MRSA isolées, et 3 MRSA sur 4 étaient multirésistantes en 2020. Aucune souche n’était résistante à la vancomycine, au linézolide ou à la mupirocine.   La surveillance des Enterococcus faecalis et Enterococcus faecium, organisée en Belgique chez les animaux producteurs de denrées alimentaires entre 2011 et 2013, et reprise en 2019, a continué. Elle permet de faire un état des lieux de la prévalence de ces bactéries commensales indicatrices et de compléter l’image de la situation de la résistance aux antimicrobiens au sein de nos élevages, complémentairement à la surveillance des E. coli indicatrices. Les entérocoques sont en effet aussi considérés comme des réservoirs de gènes de résistances aux antibiotiques, présents à la fois chez l’homme et chez les animaux. En 2020, les prévalences des espèces d’entérocoques par catégorie animale étaient similaires à celles observées en 2019. En effet, Enterococcus faecium a été plus fréquemment isolée qu’E. faecalis au sein des échantillons de poules reproductrices (88.2%), poules pondeuses (79.2%), veaux (71.7%) et porcs (67.8%). A l’inverse, Enterococcus faecalis a été isolée plus fréquemment qu’E. faecium au sein des échantillons de dindes (88.1%) et de poulets de chair (66.1%). Les tests de susceptibilité antimicrobienne réalisés cette année ont montré que, dans l’ensemble, les pourcentages de résistance observés chez Enterococcus faecalis et Enterococcus faecium au sein des différentes matrices animales étudiées semblent stables depuis 2019. Les résistances à la tétracycline, à l’érythromycine et à la quinupristine/dalfopristine étaient les résistances les plus observées, à la fois chez E. faecalis et E. faecium, en taux variable selon la matrice animale. Malgré une diminution significative de la résistance à la tétracycline (-11.2%) observée chez E. faecium isolées de porcs depuis 2019, celle-ci restait extrêmement élevée à élevée en 2020, à la fois chez E. faecalis et E. faecium isolées de poulets de chair, dindes, poules reproductrices, veaux et porcs. La résistance au chloramphénicol était particulièrement élevée chez E. faecalis isolées de veaux (43.2%) et de porcs (23.7%), bien que significativement diminuée chez les veaux depuis 2019. Particulièrement observée chez les souches isolées de poulets de chair et de dindes (30.6% et 24.1% respectivement), la résistance à l’ampicilline n’a été observée qu’au sein des E. faecium en 2020 alors qu’également observée chez E. faecalis isolées de poulets de chair, veaux et poules reproductrices en 2019. La résistance à la daptomycine a significativement diminué depuis 2019 chez E. faecium isolées de poulets de chair, poules reproductrices, poules pondeuses et veaux mais des taux modérés de résistance ont été observés en 2020 chez E. faecium isolées de poulets de chair et de dindes.  Des souches résistantes au linézolide ont également été observées en 2020, à savoir 7 E. faecalis isolées de veaux (n=5) et porcs (n=2) et 5 E. faecium isolées de poulets de chair (n=2), porcs (n =1) et veaux (n=2). Une souche E. faecalis isolée de veaux en 2020 était résistante à la vancomycine. En conclusion, au sein d’une même matrice animale, les résistances antimicrobiennes observées peuvent varier selon l’espèce bactérienne étudiée. Ainsi, les E. faecalis isolées de porcs et veaux avaient tendance à accumuler un plus grand nombre de résistances antimicrobiennes, tandis que les E. faecium isolées de poulets de chair et de dindes sont celles qui en accumulaient le plus.  Les souches E. faecalis et E. faecium isolées de poules pondeuses étaient les souches présentant le moins de résistances. Enfin, la multirésistance (résistance à au moins 3 familles d’antimicrobiens), était principalement observée chez les poulets de chair (78.2% d’E. faecalis et 68.8% d’E. faecium), les dindes (66.9% d’E. faecalis et 51.0% d’E. faecium) et les veaux (78.2% d’E. faecalis).
Keywords: AMR; Campylobacter; e.coli; Enterococcus; Salmonella; staphylococcus

Large diversity of linezolid-resistant isolates discovered in food-producing animals through linezolid selective monitoring in Belgium in 2019. - Michaël Timmermans; Bert Bogaerts; Kevin Vanneste; Sigrid C.J. De Keersmaecker; Nancy Roosens; Carole Kowalewicz; Guillaume Simon; Argudín, M Angeles; Deplano, Ariane; Hallin, Marie; P Wattiau; David Fretin; et al. (J Antimicrob Chemother, 2021)
BACKGROUND: Linezolid is a critically important antibiotic used to treat human infections caused by MRSA and VRE. While linezolid is not licensed for food-producing animals, linezolid-resistant (LR) isolates have been reported in European countries, including Belgium. OBJECTIVES: To: (i) assess LR occurrence in staphylococci and enterococci isolated from different Belgian food-producing animals in 2019 through selective monitoring; and (ii) investigate the genomes and relatedness of these isolates. METHODS: Faecal samples (n = 1325) and nasal swab samples (n = 148) were analysed with a protocol designed to select LR bacteria, including a 44-48 h incubation period. The presence of LR chromosomal mutations, transferable LR genes and their genetic organizations and other resistance genes, as well as LR isolate relatedness (from this study and the NCBI database) were assessed through WGS. RESULTS: The LR rate differed widely between animal host species, with the highest rates occurring in nasal samples from pigs and sows (25.7% and 20.5%, respectively) and faecal samples from veal calves (16.4%). WGS results showed that LR determinants are present in a large diversity of isolates circulating in the agricultural sector, with some isolates closely related to human isolates, posing a human health risk. CONCLUSIONS: LR dedicated monitoring with WGS analysis could help to better understand the spread of LR. Cross-selection of LR transferable genes through other antibiotic use should be considered in future action plans aimed at combatting antimicrobial resistance and in future objectives for the rational use of antibiotics in a One Health perspective.

Large diversity of linezolid-resistant isolates discovered in food-producing animals through linezolid selective monitoring in Belgium in 2019 - Michaël Timmermans; Bert Bogaerts; Kevin Vanneste; Sigrid C.J. De Keersmaecker; Nancy Roosens; Carole Kowalewicz; Guillaume Simon; Maria A Argudín; Deplano, Ariane; Hallin, Marie; P Wattiau; David Fretin; et al. (Journal of Antimicrobial Chemotherapy, 2021)